GLOBAL TRENDS IN SUPPORTING EDUCATIONAL AND ACADEMIC WORK AND AIMS OF THEIR INTRODUCTION IN UNIVERSITY - Larisa N. Pavlova (Вестник Российского экономического университета имени Г. В. Плеханова, 2017)
The article presents the author's view on global trends in educational and academic work and investigates its current condition. It discloses reasons and factors affecting the educational and academic work of universities, which lead to the necessity of its further development in the global system of personnel training. The author analyzes steps aimed at implementation of international treaties in the field of educational and academic work development. She compares different tools and mechanisms of supporting educational and academic work in university in view of global trends of development and their impact on quality of personnel training and introduction of continuous education system. The most acute targets of current and strategic nature are discussed. The author also explains the need to upgrade mobility of education programs and ensure their conformity with international standards.